Quantitative Analysis of Creative Thinking Skills and Concept Mastery in Physics: Temperature & Heat - Vanessa Pratiwi, Sri Mindia; Wiyono, Ketang; Ismet, Ismet; Utami , Yeni (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2025)
This study aims to identify students' creative thinking skills and concept mastery in the context of temperature and heat material at SMA Negeri 2 Palembang and to explore the relationship between these two variables. A quantitative descriptive research design was employed, involving 60 students from class XI. Data was collected using the PhysCreTHOTS test, which assesses creative thinking and concept mastery. The results showed that students' creative thinking skills averaged 48.3%, falling within the "sufficient" criteria. Specifically, scores for fluency, flexibility, originality, and elaboration were 55%, 44.9%, 44.8%, and 46.7%, respectively, all within the "sufficient" range. Concept mastery scores were 50.2% for C4, 51.9% for C5, and 46.4% for C6, indicating "moderate" criteria. A significant positive correlation (r = 0.512, p < 0.01) was found between creative thinking skills and concept mastery. The findings indicate that while students exhibit moderate levels of creative thinking and concept mastery, there is a significant relationship between these skills. This underscores the importance of fostering creative thinking to enhance conceptual mastery in physics education, especially in the context of temperature and heat materials.